The preliminary data on the spider fauna of Belgrade river islands - Dudić Boris; Žarković Luka; Ilić Bojan; Tomić Vladimir (Zaštita prirode, 2023)
This paper presents preliminary data on the spider fauna in the higher vegetation layers of four Belgrade river islands (adas) -Ada Ciganlija, Ada Međica, Veliko Ratno Ostrvo and Ada Huja. Most species belong to the families Araneidae and Thomisi-dae (7), followed by families Theridiidae (5), Salticidae (4), Linyphiidae (3), Tetraghnathidae (3), Philodromidae (2), Agelenidae (1), Oxyopidae (1), Pisauridae (1) and Uloboriade (1). The majority of collected individ-uals come from the Tetraghnathidae family. The PEN-insular river islands proved to be richer in terms of the number of recorded species and collected individuals than the true river islands. The observed anthropo-genic impact, present to a greater or lesser extent on all four Belgrade ada's, might have a negative impact on the spider fauna, which should be the subject of future research.